(untitled) (Environmental Smoke, 2024)
Measuring the well-being of a nation means identifying all the tools that enable its individuals to live well without worsening the lives of their neighbours or those to come in the future. For many years, the focus has been solely on the economic dimension, creating critical problems in the social and environmental spheres that will take years and large investments to remedy. This article gives an overview of the measurements used over the years in the international arena by recognised and respected bodies. The application of these indicators to the realities of countries has made it possible to identify models to be followed in order to enable the growth of the well-being of societies as a whole.